2004
DOI: 10.1007/978-3-540-30463-0_60
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Algorithm to Find All the Maximal Frequent Sequences in a Text

Abstract: Abstract. One of the sequential pattern mining problems is to find the maximal frequent sequences in a database with a β support. In this paper, we propose a new algorithm to find all the maximal frequent sequences in a text instead of a database. Our algorithm in comparison with the typical sequential pattern mining algorithms avoids the joining, pruning and text scanning steps. Some experiments have shown that it is possible to get all the maximal frequent sequences in a few seconds for medium texts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…We selected this system because it was one of the best in the Spanish QA task at the 2005 edition of the CLEF. We also used the data-mining tool described in [2] in order to compute the maximal frequent word sequences required by one of the methods. In this case, we established a threshold σ = 2, which indicated that a word sequence was frequent if it was contained in at least two different translations.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this system because it was one of the best in the Spanish QA task at the 2005 edition of the CLEF. We also used the data-mining tool described in [2] in order to compute the maximal frequent word sequences required by one of the methods. In this case, we established a threshold σ = 2, which indicated that a word sequence was frequent if it was contained in at least two different translations.…”
Section: Methodsmentioning
confidence: 99%
“…FSs that are not parts of any other FS are called Maximal Frequent Sequences (MFSs) [13,14]. For example, in the following text…”
Section: Maximal Frequent Sequencesmentioning
confidence: 99%
“…In any case, MFSs represent all FSs in a compact way: all FSs can be obtained from all MFSs by bursting each MFS into a set of all its subsequences. García [13] proposed an efficient algorithm to find all MFSs in a text, which we also used to efficiently obtain and store all FSs of the document.…”
Section: … Mona Lisa Is the Most Beautiful Picture Of Leonardo Da Vinmentioning
confidence: 99%
“…FSs that are not parts of any other FS are called Maximal Frequent Sequences (MFSs) [10,11]. For example, in the following text…”
Section: Frequent Sequencesmentioning
confidence: 99%
“…In any case, MFSs represent all FSs in a compact way: all FSs can be obtained from all MFSs by bursting each MFS into a set of all its subsequences. García [10] proposed an efficient algorithm to find all MFSs in a text, which we also used to efficiently obtain and store all FSs of the document.…”
Section: … Mona Lisa Is the Most Beautiful Picture Of Leonardo Da Vinmentioning
confidence: 99%